Associations of leptin levels with psychopathology, BDNF and inflammatory cytokines in patients with chronic schizophrenia as well as gender differences - Lili Zhao; Pei Tang; Haojie Fan; Mingru Hao; Xianhu Yao; Wenzheng Li; Lewei Liu; Huanzhong Liu (BMC Psychiatry)
Abstract Background Metabolic syndrome significantly contributes to mortality among individuals suffering from chronic schizophrenia (CS), and there is a strong correlation between this condition and plasma leptin (LEP) levels. However, there are relatively few studies on the factors affecting leptin levels in chronic schizophrenia, and findings are often inconsistent. The purpose of this study was to investigate the leptin levels and their association with psychopathology, BDNF and inflammatory cytokines in patients with chronic schizophrenia, as well as potential gender differences. Methods The study enrolled 301 individuals diagnosed with chronic schizophrenia. Participants were assessed for psychotic symptoms, insomnia severity, and depressive symptoms using the Positive and Negative Syndrome Scale (PANSS), Insomnia Severity Index (ISI), and Calgary Depression Scale for Schizophrenia (CDSS), respectively. Leptin, BDNF and inflammatory cytokines levels were also detected. Results Among the patients, Log LEP levels were positively correlated with females, body mass index (BMI), systolic and diastolic blood pressures, Log BDNF, Log IL-6, and Log IL-17 A levels, and negatively correlated with the total score on the PANSS, as well as scores on the positive, negative, and general psychopathology subscales (all p < 0.05). Multiple linear regression analyses revealed that Log LEP levels were independently correlated with gender (β = 0.514, t = 15.601, p < 0.001), BMI (β = 0.053, t = 12.096, p < 0.001), diastolic blood pressure (β = 0.005, t = 2.334, p = 0.020), and Log IL-17 A levels (β = 0.062, t = 2.097, p = 0.037). Notably, these associations between leptin and the above factors were only observed in the male patients. Conclusions A significant link was identified between leptin levels and the presence of psychotic symptoms, BDNF, and inflammatory cytokines (especially IL-6 and IL-17 A) in individuals suffering from chronic schizophrenia, with notable variations observed between genders. Future research, including more longitudinal studies and animal models, is necessary to delve deeper into these associations and uncover their underlying mechanisms.